Increased expression of the Th17-IL-6R/pSTAT3/BATF/Ror?T-axis in the tumoural region of adenocarcinoma as compared to squamous cell carcinoma of the lung - Balabko, Liubov; Andreev, Katerina; Burmann, Nadine; Schubert, Melanie; Mathews, Martina; Trufa, Denis; Reppert, Sarah; Rau, Tilmann; Schicht, Martin; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (Scientific Reports, 2014)
Here we describe increased expression of IL6R in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to squamous cell lung carcinoma. Moreover, here we found increased IL6R in the tumour free part of the lung. By using a murine model of lung adenocarcinoma, we discovered that few lung tumour cells expressed IL-6R and CD4+CD25+Foxp-3+ T regulatory cells down-regulated IL-6R in the tumour bearing lungs. Downstream of IL-6R, the Th17 lineage-specification factors: Signal transducer and activator of transcription 3 (STAT3), Basic leucine zipper transcription factor, BATF and a protein encoded by the RORC in human (RAR-related orphan receptor C) (ROR?T), were also found induced in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to those carrying squamous cell carcinoma. Moreover, pSTAT3 protein was found phosphorylated and auto-phosphorylated in the tumoural region of patients with adeno cell carcinoma of the lung as compared to the tumoural region of patients with squamous cell carcinoma of the lung. Intranasal application of anti-IL-6R antibodies in a murine model of lung adenocarcinoma, induced T regulatory cell markers such as Foxp3, Ctla4, Icos, Il10, Il21, Folr4 and Lag3 and inhibited Rorc in lung adenocarcinoma.
EVALuna2:4416

Interleukin-10-regulated tumour tolerance in non-small cell lung cancer - Vahl, Julius Malte; Friedrich, Juliane; Mittler, Susanne; Trump, Sonja; Heim, Lisanne; Kachler, Katerina; Balabko, Liubov; Fuhrich, Nicole; Geppert, Carol-Immanuel; Trufa, Denis; Sopel, Nina; Rieker, Ralf; et al. (British Journal of Cancer, 2017)
Lung cancer is the most life-threatening cancer type worldwide. Treatment options include surgery, radio- and chemotherapy, as well as the use of immunomodulatory antibodies. Interleukin (IL)-10 is an immunosuppressive cytokine involved in tumour immune escape.Immunohistochemistry (IHC) on human lung surgery tissue as well as human tumour cell line cultures, FACS analysis, real-time PCR and experimental lung cancer.Here we discovered a positive correlation between IL-10 and IL-10 receptor (IL-10R) expression in the lung with tumour diameter in patients with lung cancer (non-small cell lung cancer), the most life-threatening cancer type worldwide. IL-10 and IL-10R were found induced in cells surrounding the lung tumour cells, and IL-10R was mainly expressed on the surface of Foxp-3(+) T-regulatory lymphocytes infiltrating the tumour of these patients where its expression inversely correlated with programmed cell death 1. These findings were confirmed in translational studies. In a human lung adenocarcinoma cell line, IL-10R was found induced under metabolic restrictions present during tumour growth, whereby IL-10 inhibited PDL1 and tumour cell apoptosis.These new findings suggest that IL-10 counteracts IFN-? effects on PD1/PDL1 pathway, resulting in possible resistance of the tumour to anti-PD1/PDL1 immunotherapy.British Journal of Cancer advance online publication 10 October 2017 doi:10.1038/bjc.2017.336 www.bjcancer.com.
EVALuna2:6915